فاعلية التعليم عن بعد في اكتساب الكفاية الثقافية لدى متعلمي العربية من الناطقين بغيرها من وجهة نظر المعلمين والمتعلمين في مركز اللغات بالجامعة الأردنية /Effectiveness of Distance Learning on the Acquisition of Cultural Competence for Non- Arabic Speakers - Jamila Abed Abu Mughnam (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: هدفت هذه الدراسة إلى الكشف عن فاعلية التعليم عن بعد في اكتساب الكفاية الثقافية لدى الناطقين بغير العربية من وجهة نظر المعلمين والمتعلمين في مركز اللغات بالجامعة الأردنية؛ لذلك تناولت الدراسة مفهوم الكفاية الثقافية والتعليم عن بعد، وقدمت توضيحاً للمعوقات والتحديات التي تواجه عملية تعليم الثقافة عن بعد. ولقياس اتجاهات المعلمين والمتعلمين نحو فاعلية التعليم عن بعد في تحقيق الكفاية الثقافية، جُمِعت البيانات اللازمة باستخدام استبانة مكونة من (13) فقرة للمعلمين، و(13) فقرة للمتعلمين، وطُبِّقَت على عينة الدراسة المكونة من (63) متعلماً من متعلمي اللغة العربية من الناطقين بغيرها، و(21) مدرساً في شعبة اللغة العربية للناطقين بغيرها في مركز اللغات بالجامعة الأردنية. وفي ضوء المنهج الوصفي التحليلي كشفت نتائج الدراسة عن ضعف فاعليّة التعليم عن بعد في تحقيق الكفاية الثقافيّة لدى الناطقين بغير العربية من وجهة نظر المتعلّمين، وفاعلية محددة للتعليم عن بعد من وجهة نظر المعلّمين. الكلمات المفتاحية: التعليم عن بعد، اللغة العربية للناطقين بغيرها، الكفاية الثقافيّة. Abstract: This study aimed to reveal the effectiveness of distance learning in acquiring cultural competence of non-Arabic speakers from the viewpoint of teachers and learners at the Language Center - University of Jordan. Therefore, the study has looked at the concept of cultural competence and distance learning and provided an explanation of the obstacles and challenges facing the process of teaching culture in distance learning. To measure the attitudes of instructors and learners toward the effectiveness of distance learning in acquiring cultural competence. The necessary data were collected through a questionnaire consisting of (13) items for teachers and (13) items for learners, and it was applied to the study sample consisting of (63) Arabic language learners from non-native speakers, and (21) teachers in the Division of The Arabic Language for Non-Native Speakers in the Language Center - University of Jordan. In light of the descriptive analytical approach, the results of the study have revealed the poor effectiveness of distance learning in achieving cultural competence of non-Arabic speakers from the learners’ perspective, and the limited effectiveness of distance learning from the teachers’ perspectives. Keywords : distance learning, teaching Arabic for non-native speakers, cultural competence. Abstrak: Kajian ini bertujuan melihat keberkesanan pendidikan jarak jauh dalam memperoleh kecekapan budaya dalam kalangan penutur bukan Arab dari sudut pandang guru dan pelajar di Pusat Bahasa Universiti Jordan. Kajian ini membahaskan konsep kecekapan budaya dan pendidikan jarak jauh, serta memberi penjelasan tentang halangan dan cabaran yang dihadapi dalam proses pengajaran budaya dari jauh. Bagi mengukur sikap guru dan pelajar terhadap keberkesanan pendidikan jarak jauh dalam mencapai kecekapan budaya, data yang diperlukan telah dikumpulkan menggunakan soal selidik yang terdiri daripada 13 item untuk guru dan 13 item untuk pelajar. Sampel kajian terdiri daripada 63 orang pelajar bahasa Arab sebagai bahasa kedua serta 21 orang guru di Jabatan Bahasa Arab sebagai Bahasa Kedua di Pusat Bahasa - Universiti Jordan. Berdasarkan pendekatan analisis deskriptif, hasil kajian mendedahkan bahawa keberkesanan pendidikan jarak jauh dalam mencapai kecekapan budaya dalam kalangan penutur bukan Arab adalah lemah dari sudut pandang pelajar. Manakala, dari sudut pandang guru keberkesanan pendidikan jarak jauh adalah terhad. Kata kunci: pendidikan jarak jauh, bahasa Arab untuk bukan penutur asli, kecekapan budaya.